A silicon-free carbon-ceramic composite material and a preparation method thereof

By using organic binders to cover silicon powder at room temperature, the problem of silicone adhesion in the preparation of silicon seepage silicon is solved, and the easy separation and low -cost production of products and crickets are realized.

CN119143518BActive Publication Date: 2025-01-28CHENGDU CARBON
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411639199.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-28
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

In the process of melting silicon seeping of carbon ceramic composite materials, the silicon liquid easily adheres to the product and the crucible surface after cooling, resulting in difficulty in cleaning the product and crucible, affecting the product quality and service life of the crucible.

Method used

Using organic adhesives at room temperature to wrap the surface of the silicon powder a layer of ceramic isolation powder, and cover it through drum grinding, which significantly improves the adhesion of the silicon hydrocephaly after silicon.

Benefits of technology

After the silicon is achieved, there is no obvious adhesion for the product and the surface of the cricket.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143518B_ABST
    Figure CN119143518B_ABST
Patent Text Reader

Abstract

The present invention discloses a carbon-ceramic composite material without silicon adhesion and a preparation method thereof, belonging to the technical field of carbon-ceramic composite materials. The preparation method comprises: coating silicon powder with a ceramic insulating material by roller grinding at room temperature, and subjecting the coated silicon powder to siliconization reaction with a carbon-carbon composite material after high-temperature treatment; wherein the ceramic insulating material comprises carbon element powder, ceramic powder, organic binder powder and solvent. The preparation method of the present invention is simple to operate and has stable quality. It is suitable for a variety of siliconization treatments such as single-sided, double-sided, and embedded, and is suitable for mass production. The surface of the obtained carbon-ceramic composite material is clean and has no obvious silicon adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon-ceramic composite materials, in particular to a carbon-ceramic composite material without silicon adhesion and a preparation method thereof. Background Art

[0002] Melt siliconization is one of the mainstream technologies for the industrial preparation of carbon-ceramic composite materials. The process involves allowing the molten silicon powder to enter the interior of the carbon-carbon composite through capillary reaction, infiltrate and react with the matrix carbon to form SiC / C composite materials. It was found in production that in the preparation of carbon-ceramic composite materials by melt siliconization, the molten flowing silicon liquid often adheres to the surface of the product and the crucible after cooling, resulting in silicon adhesion on the surface of the product and the inner wall of the crucible, making it difficult to clean and separate the product and the crucible, affecting product quality, crucible service life, etc., and generating additional labor costs and auxiliary material consumption.

[0003] The prior art CN113773094A discloses a solution for forming a breakable silicon carbide / silicon nitride thin shell on the surface of silicon powder, which can effectively improve the problems of pore blockage and uneven siliconization during the siliconization process. However, in this technical solution, the silicon powder needs to be pretreated at a high temperature of 1400°C before use, which has high requirements on equipment and consumes a lot of energy. Summary of the invention

[0004] In order to solve the above-mentioned problems of the prior art, the purpose of the present invention is to provide a new method for preparing a carbon-ceramic composite material. In this method, a layer of ceramic isolation powder is wrapped on the surface of silicon powder with an organic binder at room temperature, which significantly improves the problem of large-area adhesion of silicon liquid to products and crucibles after siliconization. After siliconization, there is no obvious adhesion on the surface of the product and the crucible, and the product and the crucible are easy to separate. At the same time, the method is simple to operate, low in cost, and can be industrialized for mass production.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a carbon-ceramic composite material without silicon adhesion, comprising:

[0007] At room temperature, coating silicon powder with a ceramic insulating material to obtain coated silicon powder;

[0008] The coated silicon powder and the high-temperature treated carbon-carbon composite material are subjected to siliconization reaction to obtain a carbon-ceramic composite material without silicon adhesion;

[0009] Wherein, the coating is achieved by roller grinding; the raw material components of the ceramic isolation material include powder and solvent, wherein the powder includes: 10-40 parts by mass of carbon element powder, 10-40 parts by mass of ceramic powder and 30-50 parts by mass of organic binder powder, and the mass of the solvent is 150-200% of the mass of the powder.

[0010] The above technical scheme of the present invention can prepare carbon element powder, ceramic powder, organic binder powder and solvent into a coating slurry, wherein the organic binder wraps the ceramic powder and carbon powder around the metal silicon powder. During the heating process, the organic binder is gradually carbonized, and together with the coated ceramic and carbon powder, a loose isolation shell is formed on the surface of the metal silicon. After the metal silicon powder is melted, the loose isolation shell forms a steric hindrance between the metal silicon powders, making it difficult for the residual silicon liquid after siliconization to adhere densely and agglomerate over a large area.

[0011] Preferably, the mass of the silicon powder is 8-30 times the mass of the ceramic isolation material.

[0012] More preferably, the mass of the silicon powder is 8-10 times the mass of the ceramic insulating material.

[0013] Preferably, the purity of the silicon powder is ≥98% and the particle size is ≥40 mesh.

[0014] Preferably, the carbon powder has a particle size D 50 Carbon powder ≤30μm.

[0015] Preferably, the ceramic powder is selected from a particle size D 50 One or more of boron nitride powder, silicon carbide powder, silicon nitride powder and silicon dioxide powder with a particle size of ≤30 μm.

[0016] Preferably, the organic binder powder is powder of an organic binder resin, and the organic binder resin is selected from one or more of phenolic resin, epoxy resin, furan resin, polyvinyl butyral, and polyvinyl alcohol.

[0017] Preferably, the solvent is anhydrous ethanol or water.

[0018] Preferably, the preparation of the ceramic isolation material comprises: wet ball milling the powder and the solvent, wherein the ball-to-material ratio is 5-7:1.

[0019] Preferably, the treatment process of the siliconizing reaction includes: slowly heating the carbon-carbon composite material after high-temperature treatment and the coated silicon powder or the preheated coated silicon powder to 1450-1700° C. and keeping the temperature.

[0020] Preferably, the preparation method specifically comprises:

[0021] The powder and the solvent are wet ball-milled to obtain an isolation slurry; wherein the ball-to-material ratio is 5-7:1, and the balls used are zirconium oxide balls with a diameter of 5 mm;

[0022] Adding the silicon powder to the isolation slurry, performing roller grinding, and then drying to obtain the coated silicon powder;

[0023] The coated silicon powder and the high-temperature treated carbon-carbon composite material are slowly heated to 600-900° C., kept warm for 1-2 hours, and then continued to be heated to 1500-1700° C. and kept warm for 2-4 hours to obtain the carbon-ceramic composite material without silicon adhesion.

[0024] Preferably, the slow heating rate is 0.5-1°C / min.

[0025] Or, preferably, the preparation method specifically comprises:

[0026] The powder and the solvent are wet ball-milled to obtain an isolation slurry; wherein the ball-to-material ratio is 5-7:1, and the balls used are zirconium oxide balls with a diameter of 5 mm;

[0027] Adding the silicon powder to the isolation slurry, performing roller grinding, and then drying to obtain the coated silicon powder;

[0028] Slowly heating the coated silicon powder to 400-600° C. in a vacuum or inert atmosphere, keeping the temperature for 1-2 hours, and then cooling to obtain preheated coated silicon powder;

[0029] Preferably, the slow heating rate is 0.5-1°C / min.

[0030] The preheated coated silicon powder and the high-temperature treated carbon-carbon composite material are heated to 1500-1700° C. and kept warm for 2-4 hours to obtain the carbon-ceramic composite material without silicon adhesion.

[0031] The present invention further provides a carbon-ceramic composite material without large-area adhesion of silicon liquid prepared according to the above preparation method. After siliconization, the composite material is easy to separate from the crucible, and the remaining silicon slag in the crucible is in a fluffy granular form and easy to clean. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a scanning electron microscope image of the coated silicon powder obtained in Example 1.

[0033] Figure 2 The actual (a) and scanning electron microscope (b) comparison pictures of the remaining fluffy silicon slag after siliconization obtained in Example 1.

[0034] Figure 3 The comparative observation results of surface adhesion and residual silicon slag of the carbon-ceramic composite materials obtained at different coating ratios in Example 1, wherein the mass ratio of carbon powder to boron nitride powder in (a) is 40:10, the mass ratio of carbon powder to boron nitride powder in (b) is 25:25, and the mass ratio of carbon powder to boron nitride powder in (c) is 10:40.

[0035] Figure 4The figures are comparative observation results of the silicon liquid adhesion of the uncoated silicon powder and the carbon-ceramic composite materials corresponding to the coated silicon powder in different ratios in Example 2, wherein (a) is the case of uncoated silicon powder, (b) is the case of a mass ratio of metal silicon powder to slurry of 30:1, (c) is the case of a mass ratio of metal silicon powder to slurry of 20:1, and (d) is the case of a mass ratio of metal silicon powder to slurry of 10:1.

[0036] Figure 5 The comparison observation results of silicon adhesion and residual silicon slag of the carbon-ceramic composite materials corresponding to the coated silicon powders in different proportions in Example 3, wherein the mass ratio of the metal silicon powder to the slurry in (a) is 20:1, and the mass ratio of the metal silicon powder to the slurry in (c) is 10:1. DETAILED DESCRIPTION

[0037] The technical scheme of the present invention will be further described below in conjunction with the embodiments and drawings of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0038] Example 1

[0039] The carbon-ceramic composite material was prepared by the following steps:

[0040] (1) As shown in Table 1, weigh the corresponding mass proportions of carbon powder, polyvinyl alcohol 2688 and boron nitride powder respectively, and then weigh φ5mm zirconium oxide balls at a ball-to-material ratio of 5-7:1, put them into a polytetrafluoroethylene ball mill, then add pure water with a mass of 200% of the mass of the mixed powder, and ball mill the mixture for 12 hours;

[0041] Table 1

[0042]

[0043] (2) adding metal silicon powder with a mass particle size of 2-5 mm and a purity of 99.99% to the slurry obtained in step (1), with the mass ratio of metal silicon powder to slurry being 10:1, and then rolling for 1 hour and drying to obtain covered silicon powder;

[0044] (3) slowly heating the covered silicon powder to 500° C. at a heating rate of 0.5° C. / min under vacuum or inert gas protection and keeping the temperature for 1 hour to obtain heated covered silicon powder;

[0045] (4) The carbon-carbon composite material treated at a high temperature of ≥1900° C. and the heated covered silicon powder obtained in step (3) are heated to 1650° C. in a siliconizing furnace and kept at this temperature for 3 hours to obtain a carbon-ceramic composite material.

[0046] The microstructure of the covered silicon powder obtained was characterized, and the obtained scanning electron microscope image is shown in the attached figure. Figure 1 As shown, it can be seen that a shell mainly composed of ceramic powder is successfully wrapped around the metal silicon powder.

[0047] The silicon slag formed by the silicon powder after siliconization was observed physically and microscopically. The results are shown in the attached figure. Figure 2 As shown, it can be seen that the residual silicon slag after siliconization is fluffy, which is mainly the ceramic powder-coated shell left after the silicon liquid is sucked away by capillaries.

[0048] The surface adhesion and residual silicon slag of the carbon-ceramic composite material with different coating ratios obtained in Example 1 were observed and tested, and the results are shown in the attached figure. Figure 3 As shown, it can be seen that the three ratios of coated silicon powder can effectively improve the adhesion of silicon powder, and with the increase of the proportion of ceramic powder, the integrity of the residual silicon slag after siliconization is enhanced.

[0049] Example 2

[0050] The carbon-ceramic composite material was prepared by the following steps:

[0051] (1) Weigh 10 parts by weight of D 50 ≤30μm carbon powder, 50 parts by mass of phenolic resin and 40 parts by mass of D 50 ≤30μm silicon carbide powder, and then weigh φ5mm zirconium oxide balls at a ball-to-material ratio of 5-7:1, put them into a polytetrafluoroethylene ball mill, then add anhydrous ethanol with a mass of 150% of the mass of the mixed powder, and ball mill the mixture for 12 hours;

[0052] (2) adding metal silicon powder with a mass particle size of 2-5 mm and a purity of 99.99% to the slurry obtained in step (1), with the mass ratio of metal silicon powder to slurry being 30:1, 20:1 and 10:1, followed by rolling for 1 hour and drying to obtain covered silicon powder;

[0053] (3) The carbon-carbon composite material treated at a high temperature of ≥1900°C and the covered silicon powder obtained in step (2) are slowly heated to 600°C at a heating rate of 0.5°C / min in a siliconizing furnace and kept at this temperature for 1 hour, and then the temperature is further raised to 1650°C and kept at this temperature for 3 hours to obtain a carbon-ceramic composite material.

[0054] The carbon-ceramic composite material obtained by the same siliconization treatment with uncoated silicon powder and the carbon-ceramic composite material obtained in Example 2 with different silicon powder and slurry ratios were observed and tested for the adhesion of silicon liquid on the contact surface with silicon powder. The results are shown in the attached figure. Figure 4As shown, it can be seen that the silicon powder after coating treatment has a significant improvement in the adhesion of silicon liquid after preparation of carbon-ceramic composite materials, and with the increase of the coating slurry ratio, the adhesion improvement of the silicon powder contact surface of the carbon-ceramic composite is more significant. When the ratio of silicon powder to slurry is 10:1, there is no obvious silicon liquid adhesion on the surface of the carbon-ceramic composite.

[0055] Example 3

[0056] The carbon-ceramic composite material was prepared by the following steps:

[0057] (1) Weigh 10 parts by weight of D 50 ≤30μm carbon powder, 50 parts by mass of polybutyral 60H and 40 parts by mass of D 50 ≤30μm silicon nitride powder, and then weigh φ5mm zirconium oxide balls at a ball-to-material ratio of 5-7:1, put them into a polytetrafluoroethylene ball mill, then add anhydrous ethanol with a mass of 200% of the mass of the mixed powder, and ball mill the mixture for 12 hours;

[0058] (2) adding metal silicon powder with a mass particle size of 2-5 mm and a purity of 99.99% to the slurry obtained in step (1), with the mass ratio of metal silicon powder to slurry being 20:1 and 10:1, followed by rolling for 1 hour and drying to obtain covered silicon powder;

[0059] (3) The carbon-carbon composite material treated at a high temperature of ≥1900°C and the covered silicon powder obtained in step (2) are slowly heated to 600°C at a heating rate of 0.5°C / min in a siliconizing furnace and kept at this temperature for 1 hour, and then the temperature is further raised to 1650°C and kept at this temperature for 3 hours to obtain a carbon-ceramic composite material.

[0060] The surface adhesion of the carbon-ceramic composite material obtained at different silicon powder to slurry ratios in Example 3 and the residual silicon slag were compared and observed. The results are shown in the attached figure. Figure 5 As shown, it can be seen that with the increase of coating slurry, the improvement of surface silicon adhesion of carbon-ceramic composite material is more obvious, the integrity of residual silicon slag after siliconization is better, and when the ratio of silicon powder to slurry is 10:1, there is no obvious silicon liquid adhesion on the surface of carbon-ceramic composite.

[0061] All other embodiments obtained by ordinary technicians in this field without making any creative work should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a carbon-ceramic composite material without silicon adhesion, characterized in that: It includes: At room temperature, coating silicon powder with a ceramic insulating material to obtain coated silicon powder; The coated silicon powder and the high-temperature treated carbon-carbon composite material are subjected to siliconization reaction to obtain a carbon-ceramic composite material without silicon adhesion; The coating is achieved by roller grinding; the mass ratio of the silicon powder to the ceramic isolation material is 8-30:1; the raw material components of the ceramic isolation material include powder and solvent, the mass of the solvent is 150-200% of the mass of the powder; the powder includes: 10-40 parts by mass of carbon powder, 10-40 parts by mass of ceramic powder and 30-50 parts by mass of organic binder powder; the carbon powder has a particle size D 50 ≤30μm carbon powder and / or graphite powder; the ceramic powder is selected from the group consisting of 50 One or more of boron nitride powder, silicon carbide powder, silicon nitride powder and silicon dioxide powder with a particle size of ≤30 μm; the solvent is anhydrous ethanol and / or water.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the silicon powder to the ceramic isolation material is 8-10:

1.

3. The preparation method according to claim 1, characterized in that: The organic binder powder is powder of an organic binder resin, and the organic binder resin is selected from one or more of phenolic resin, epoxy resin, furan resin, polyvinyl butyral, and polyvinyl alcohol.

4. The preparation method according to claim 1, characterized in that: The purity of the silicon powder is ≥98% and the particle size is ≥40 meshes.

5. The preparation method according to claim 1, characterized in that: The preparation of the ceramic isolation material comprises: wet ball milling the powder and the solvent, wherein the ball-to-material ratio is 5-7:

1.

6. The preparation method according to claim 1, characterized in that: The siliconizing reaction process includes: slowly heating the high-temperature treated carbon-carbon composite material and the coated silicon powder or the preheated coated silicon powder to 1450-1700° C. and keeping the temperature.

7. The preparation method according to claim 1, characterized in that: Specifically include: The powder and the solvent are wet ball-milled to obtain an isolation slurry; wherein the ball-to-material ratio is 5-7:1, and the balls used are zirconium oxide balls with a diameter of 5 mm; Adding the silicon powder to the isolation slurry, performing roller grinding, and then drying to obtain the coated silicon powder; The coated silicon powder and the high-temperature treated carbon-carbon composite material are slowly heated to 600-900° C., kept warm for 1-2 hours, and then continued to be heated to 1500-1700° C. and kept warm for 2-4 hours to obtain the carbon-ceramic composite material without silicon adhesion.

8. The preparation method according to claim 1, characterized in that: Specifically include: The powder and the solvent are wet ball-milled to obtain an isolation slurry; wherein the ball-to-material ratio is 5-7:1, and the balls used are zirconium oxide balls with a diameter of 5 mm; Adding the silicon powder to the isolation slurry, performing roller grinding, and then drying to obtain the coated silicon powder; Slowly heating the coated silicon powder to 400-600° C. in a vacuum or inert atmosphere, keeping the temperature for 1-2 hours, and then cooling to obtain preheated coated silicon powder; The preheated coated silicon powder and the high-temperature treated carbon-carbon composite material are heated to 1500-1700° C. and kept warm for 2-4 hours to obtain the carbon-ceramic composite material without silicon adhesion.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The heating rate of the slow heating is 0.5-1°C / min.

10. A carbon-ceramic composite material without silicon adhesion prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Treatment method of silicon powder for molten silicon infiltration

    CN113773094A

  • Diphase nanometer strengthened metal matrix micro-nanometer power and preparation method thereof with both antifriction and wear-resistant effects

    CN102990063A

  • Core-shell structure silicon-carbon composite material as well as preparation method and application thereof

    CN106058228A